Clinical case of treatment of hemoptysis in an adult patient with Eisenmenger syndrome by closing systemic pulmonary collateral arteries - Radchenko, M. P.; Dovgalyuk, A. A.; Kuzmenko, Yu. L.; Rudenko, N. M. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Dilated bronchial arteries and systemic to pulmonary collateral arteries (aorto-pulmonary collateral arteries) can cause hemoptysis and accompany congenital heart defects (CHD). For diagnostic verification of aforementioned vessels selective angiography is method of choice. The purpose of this article is to present a clinical case of successful hemoptysis treatment by endovascular closure of systemic to pulmonary collateral arteries in an adult patient. Material and methods. Patient has been observed at the Ukrainian Children’s Cardiac Center from 2014, among complains: shortness of breath, fatigue, and cyanosis. For last two months patient had frequent episodes of hemoptysis after minimal physical activity. Results. Patient undergone an endovascular intervention with the closure of the systemic to pulmonary collaterals. On control angiography blood flow through occluded systemic to pulmonary arteries has been absent. For patients with complex congenital heart disease, complicated by pulmonary hypertension, the solution of this problem is endovascular intervention. Conclusion. Embolization of systemic to pulmonary collateral arteries is an effective procedure for treating patients with haemoptysis.